Acute pancreatitis and diabetes mellitus: a review - Allyson Richardson; Walter G. Park (The Korean Journal of Internal Medicine, 2021)
Diabetes following acute pancreatitis (AP) is becoming increasingly recognized. It is unclear what subtype of diabetes mellitus (DM) occurs; however, type 3c diabetes mellitus (T3cDM) is gaining increasing recognition. T3cDM has differing pathophysiology than other subtypes of DM and therefore differing disease course and treatment. Current studies have examined the incidence and prevalence of DM following AP, and meta-analyses have shown around 15% develop DM at 1 year with an increasing proportion developing DM at 5 years. It has been observed that some patients have transient hyperglycemia following AP episode with a subset developing persistent impaired glucose metabolism; however, the exact timeline is not well defined. The data on risk factors for developing DM after AP is limited and mixed; however, it is likely that severity of AP may impact the propensity to develop DM. Screening guidelines have not been established following AP; however, screening 1-year post-event will likely capture a sizable proportion of newly developed DM. The endocrine and exocrine pancreas are closely linked, and studies have found significant overlap in dysfunction of both after AP. Finally, there are some data to suggest that diabetes predisposes patients to structural changes in the pancreas and increased risk of developing AP.